The development of loop-mediated isothermal amplification targeting alpha-tubulin DNA for the rapid detection of Plasmodium vivax - Dinzouna-Boutamba, Sylvatrie-Danne (BioMed Central, 2014)
BACKGROUND: Malaria that is caused by Plasmodium vivax is the most widely distributed human malaria. Its recent resurgence in many parts of the world, including the Republic of Korea (ROK), emphasizes the importance of improved access to the early and accurate detection of P. vivax to reduce disease burden. In this study, a rapid and efficient loop-mediated isothermal amplification (LAMP)-based method was developed and validated using blood samples from malaria-suspected patients. METHOD: A LAMP assay targeting the α-tubulin gene for the detection of P. vivax was developed with six primers that recognize different regions of the target gene. The diagnostic performance of the α-tubulin LAMP assay was compared to three other tests: microscopic examinations, rapid diagnostic tests (RDTs), and nested polymerase chain reactions (PCRs) using 177 whole blood specimens obtained from ROK military personnel from May to December 2011. RESULTS: The α-tubulin LAMP assay was highly sensitive with a detection limit of 100 copies of P. vivax α-tubulin gene per reaction within 50 min. It specifically amplified the target gene only from P. vivax. Validation of the α-tubulin LAMP assay showed that the assay had the highest sensitivity (P < 0.001 versus microscopy; P = 0.0023 versus RDT) when nested PCR was used as the gold standard and better agreement (concordance: 94.9%, kappa value: 0.865) with nested PCR than RDT and microscopy. A Receiver Operation Characteristics analysis showed that the diagnostic accuracy of the α-tubulin LAMP assay for vivax malaria was higher (Area Under Curve = 0.908) than RDT and microscopy. CONCLUSION: This study showed that the P. vivax α-tubulin LAMP assay, which can be used to diagnose early infections of vivax malaria, is an alternative molecular diagnostic tool and a point-of-care test that may help to prevent transmission in endemic areas.